2020
DOI: 10.1108/md-10-2019-1402
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking risk management in entrepreneurial SMEs: towards the integration with the decision-making process

Abstract: PurposeThe main purpose of this study is twofold: first, to analyze how risk is considered and managed by entrepreneurial SMEs, where the original founder is still the entrepreneur running the business, and second to understand if risk management is integrated with decision making.Design/methodology/approachThis research is based on a multiple case study. Three entrepreneurial SMEs based in the North-West of Italy were selected to obtain a heterogeneous sample. They operate in the manufacturing sector and they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 81 publications
3
44
0
4
Order By: Relevance
“…The lack of adequate refinement of risk management procedures in, among others, Polish enterprises was also indicated in the research by , where the reason for this state of affairs was given, among others, in the inappropriate attitude of managers to risk, as well as their lack of knowledge and experience in risk management. These results are also consistent with the studies by Crovini et al (2020), where it was indicated that the risk management process was not always formalized, but an unconscious, intuitive risk analysis was always performed. In turn, studies by Britzelmaier et al (2015) carried out on German companies proved that risk management was most often used by large entities, therefore the use of this process in small and medium-sized enterprises played a minor role.…”
Section: Discussionsupporting
confidence: 91%
“…The lack of adequate refinement of risk management procedures in, among others, Polish enterprises was also indicated in the research by , where the reason for this state of affairs was given, among others, in the inappropriate attitude of managers to risk, as well as their lack of knowledge and experience in risk management. These results are also consistent with the studies by Crovini et al (2020), where it was indicated that the risk management process was not always formalized, but an unconscious, intuitive risk analysis was always performed. In turn, studies by Britzelmaier et al (2015) carried out on German companies proved that risk management was most often used by large entities, therefore the use of this process in small and medium-sized enterprises played a minor role.…”
Section: Discussionsupporting
confidence: 91%
“…Secondly, exposure of two emerging themes; 1) decision-making process and their relation with SMEs stakeholders, and 2) knowledge about environmental themes as materials and resources, presenting their difference between the countries. These aspects require more study at the local level, can complement and enhance ES (Crovini et al 2020). Finally, the comparative analysis demonstrates the relevance of institutional context and the environmental legislation's potential effects in these mentioned aspects, especially CSR (Graafland and Smid 2017).…”
Section: Theoretical Contributionsmentioning
confidence: 93%
“…De acordo com Tosi Jr. e Slocum Jr. (1984) não existe um modelo passível de ser considerado "melhor", mas existem maneiras de elaboração de um plano contingencial menos abrangentes ou difíceis de aplicação. Os autores ainda dissertam sobre a importância da adaptação da empresa diante do seu ambiente externo para que seja possível que planos de contingenciamento sejam criados e postos em práticas em momentos de turbulência (DRENNAN, 2006;CROVINI;SANTORO;OSSOLA, 2020;MCCONNELL).…”
Section: Gerenciamento De Crise E Planos De Contingência: Qual a Importância Em Micro E Pequenas Empresas?unclassified